2017
DOI: 10.1002/maco.201609300
|View full text |Cite
|
Sign up to set email alerts
|

High temperature corrosion in molten solar salt: The role of chloride impurities

Abstract: The role of chloride impurities in molten NaNO3‐KNO3 (solar salt) mixture on corrosion behavior of low‐chromium ferritic‐martensitic X20CrMoV11‐1 steel (X20) and stainless steel 316 (SS316) was studied at 600 °C. Gravimetric and metallographic methods were employed to characterize the kinetics of oxidation and the resulting corrosion products. Steel X20 showed non‐protective character in both low‐ (up to 0.02 wt% Cl−) and high‐ (up to 0.25 wt% Cl−) chloride salts by forming a thick and non‐compact oxide scale.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…This is in good agreement with the study by Audigié et al showing the formation of NaFeO 2 in the multi-layered oxide scale grown on P91 during exposure in molten nitrates at 580 • C [25]. The incorporation of Na into the oxide scales and the consequential formation of sodium ferrite is attributed to the transfer of Na cations from the salt melt to the scale surface and their inward penetration through oxide scale defects such as pores and cracks [18]. Moreover, N was enriched underneath the porous oxide scale (see Figure 7b and N map in Figure 7c), suggesting the nitridation of the sub-scale region, which was also observed in other studies investigating the molten nitrate corrosion of this alloy at 580 • C [6,25].…”
Section: Scaling Behavior Of Uncoated P91supporting
confidence: 92%
See 2 more Smart Citations
“…This is in good agreement with the study by Audigié et al showing the formation of NaFeO 2 in the multi-layered oxide scale grown on P91 during exposure in molten nitrates at 580 • C [25]. The incorporation of Na into the oxide scales and the consequential formation of sodium ferrite is attributed to the transfer of Na cations from the salt melt to the scale surface and their inward penetration through oxide scale defects such as pores and cracks [18]. Moreover, N was enriched underneath the porous oxide scale (see Figure 7b and N map in Figure 7c), suggesting the nitridation of the sub-scale region, which was also observed in other studies investigating the molten nitrate corrosion of this alloy at 580 • C [6,25].…”
Section: Scaling Behavior Of Uncoated P91supporting
confidence: 92%
“…Furthermore, commercial solar salt contains a wide variety of impurities, such as chlorides and sulfates, which can increase the corrosion rate, as shown in [17,18]. Due to the above stated reasons, the corrosion resistance of structural materials employed in the receiver tubing system and the hot storage tank is a decisive factor for plant design and lifetime [4,6,[9][10][11]19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that the corrosion loss of mild steel, immersed for several hours in melts at 600 °C, was significantly increased by adding 7.5 wt.% Na 2 SO 4. What's more, Dorcheh et al . also studied the corrosion behavior of X20 steel and SS316 in molten solar salt at 600 °C.…”
Section: Introductionmentioning
confidence: 90%
“…Material selection and lifetime estimation are challenging tasks due to the variety of degradation mechanisms occurring at the external and internal surfaces of the absorber tube. With regards to the inside of the tube, the nitrite and nitrate anions in combination with O 2 and salt impurities such as chlorides form a highly corrosive and challenging environment [2][3][4]. With respect to the outside of the absorber tube, the materials are concurrently exposed to dust erosion as well as thermocyclic oxidation due to fluctuating temperature.…”
Section: Introductionmentioning
confidence: 99%